Evidence that the prevalence of childhood overweight is plateauing: data from nine countries. - Olds, T; Aeberli, I; Maher, C (My University, 2013)
Until quite recently, there has been a widespread belief in the popular media and scientific literature that the prevalence of childhood obesity is rapidly increasing. However, high quality evidence has emerged from several countries suggesting that the rise in the prevalence has slowed appreciably, or even plateaued. This review brings together such data from nine countries (Australia, China, England, France, Netherlands, New Zealand, Sweden, Switzerland and USA), with data from 467,294 children aged 2 – 19 years. The mean unweighted rate of change in prevalence of overweight and obesity was 0.00 (0.49)% per year across all age sex groups and all countries between 1995 and 2008. For overweight alone, the fi gure was 0.01 (0.56)%, and for obesity alone 0.01 (0.24)%. Rates of change differed by sex, age, socioeconomic status and ethnicity. While the prevalence of overweight and obesity appears to be stabilizing at different levels in different countries, it remains high, and a signifi cant public health issue. Possible reasons for the apparent flattening are hypothesised.
Keywords: Health -- Obesity; Children; Health and wellbeing; Children; Health; Obesity; Health and wellbeing